Pengaruh Alat Pembayaran Dengan Menggunakan Kartu, Dana Float dan Kebijakan Moneter Terhadap Velocity of Money di Indonesia - Mustika Sasikarani; Thomas Andrian (Jurnal Indonesia Sosial Teknologi, 2022)
The increase in the use of non-cash will reduce the use of cash (cards) to increase the efficiency of transaction settlement, this will have an impact on the velocity of money. In addition, the decrease in cash circulating in the community due to the transition to non-cash money is not entirely used for transaction activities, most of the non-cash money will also settle and the deposited funds will be invested by the issuer in Government Securities and Bank Indonesia. The purpose of this study was to determine the effect of the value of credit card transactions on the velocity of money in Indonesia, to determine the effect of the value of ATM/debit card transactions on the velocity of money in Indonesia, to understand the impact of floating funds on the velocity of money in Indonesia and to determine the effect of policy interest rates (BI Rate). and BI7DRR) on the velocity of money in Indonesia. The type of approach used in this study is a quantitative descriptive approach. The analytical tool used is an error correction model (ECM) which is commonly used in econometrics. Credit card transaction value (NTKK) Significant positive impact on short-term and long-term currency turnover in Indonesia. In Indonesia's short and long term, the amount of floating funds (JDF) has a significant negative effect on Indonesia's short-term currency turnover, and the policy interest rate/BI Rate and BI7DRR (SBK) do not have a significant impact on short-term and long-term currency turnover in Indonesia